Engineering thermodynamics and fluid mechanics - Nag,P.K (Tata McGraw-Hill, 2010)
Engineering thermodynamics and fluid mechanics / Nag,P.K.. -- New Delhi: Tata McGraw-Hill, 2010 536.7 N147 No. of Copies : 1